2016
DOI: 10.1002/micr.30048
|View full text |Cite
|
Sign up to set email alerts
|

Distally based subcutaneous veins for venous insufficiency of the reverse posterior interosseous artery flap

Abstract: Subcutaneous veins may be reliable and useful for overcoming major drawbacks associated with reverse flow posterior interosseous artery flap and for diminishing flap loss due to venous insufficiency. © 2016 Wiley Periodicals, Inc. Microsurgery 36:384-390, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…The PIA flap congestion ranges from 8 to 25% in the literature [12] ; however, we had a congestion rate of 21.4%, which can be due to vigilant maneuvers we opted to prevent this complication. There are a number of ways to prevent venous congestion, avoiding the dissection of the AIA and PIA communicating branch, venous supercharging [ 6 , 13 ] where deem indicated, creating a cutaneous handle which covers a distal flap pedicle, and avoiding the subcutaneous tunneling of the pedicle [14] . We practice harvesting, as previously described, racquet-shaped flap [15] , which allows a easy flap inset and enhances a venous outflow as the skin bridge contains the subcutaneous venous plexus, but to include this distal skin paddle, we suggest to shift the distal marking to the ulnar head to reliably cover the vascular pedicle.…”
Section: Discussionmentioning
confidence: 99%
“…The PIA flap congestion ranges from 8 to 25% in the literature [12] ; however, we had a congestion rate of 21.4%, which can be due to vigilant maneuvers we opted to prevent this complication. There are a number of ways to prevent venous congestion, avoiding the dissection of the AIA and PIA communicating branch, venous supercharging [ 6 , 13 ] where deem indicated, creating a cutaneous handle which covers a distal flap pedicle, and avoiding the subcutaneous tunneling of the pedicle [14] . We practice harvesting, as previously described, racquet-shaped flap [15] , which allows a easy flap inset and enhances a venous outflow as the skin bridge contains the subcutaneous venous plexus, but to include this distal skin paddle, we suggest to shift the distal marking to the ulnar head to reliably cover the vascular pedicle.…”
Section: Discussionmentioning
confidence: 99%
“…The major disadvantage of the PIAF is venous congestion problems that can occur because it is a reverse flap (Balakrishnan, Kumar, & Hussain, 2003;Brunelli, Valenti, Dumontier, Panciera, & Gilbert, 2001;Dogra, Singh, Chakravarty, & Basu, 2006;Ege, Tuncay, & Ercetin, 2003;Lu, Gong, Lu, & Wang, 2007). Many modifications have been described to overcome these venous problems, including using a wider pedicle to raise the flap, adding a fascia to the pedicle, adding a superficial vein to the pedicle, and making venous anastomoses (Acharya, Bhat, & Bhaskaranand, 2012;Fong & Chew, 2014;Ozalp, Elbey, Aydin, & Ozkan, 2016;Yazar, Chen, & Mardini, 2008). In this report, we present our experience with venous super-drained posterior interosseous artery flaps VS-PIAF for reconstruction of hand defects of 17 patients, which we performed using a distal end-to-end superficial venous anastomosis to overcome venous congestion problems.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous methods have been proposed to overcome venous insufficiency with PIAFs.Ozalp et al have proposed adding a superficial vein to the pedicle(Ozalp et al, 2016), and Acharya et al have suggested some modifications, such as creating a broad pedicle with a cutaneous handle and avoiding tunneling for the inset(Acharya et al, 2012).Chen et al used a wide base to incorporate both branches from the anterior and posterior interosseous arteries in elderly patients and performed additional venous anastomoses in cases where venous congestion was identified after the flap inset (Chen et al, 1998). Using a broad pedicle will enhance the venous return because the wider pedicle does not twist as easily as a thin one, but the cost is a reduction in pedicle mobility.…”
mentioning
confidence: 99%
“…The reverse posterior interosseous artery flap can be applied in cases with ulnar or radial artery disruption to cover skin defects over the distal forearm without sacrificing the major vessels. However, it requires the retrograde dissection of the vascular pedicle through the fascial septum, and there is the potential for posterior interosseous nerve injury when raising the flap (Buchler & Frey, 1991) and postoperative venous congestion (Akinci, Ay, Kamiloglu, & Erçetin, 2006;Özalp, Elbey, Aydin, & Özkan, 2016). Moreover, retrospective clinical studies on the posterior interosseous artery flap reported that the posterior interosseous artery was absent or unusable in some cases (Cavadas, 1999;Dadalt Filho, Ulson, & Penteado, 1994;Giunta & Lukas, 1998).…”
Section: Introductionmentioning
confidence: 99%